Application of HRM-PCR (high resolution melting PCR) for identification of forensically important Coleoptera species. Issue 1 (December 2019) - Malewski, Tadeusz; Łoś, Marta; Sołtyszewski, Ireneusz
Abstract: Precise estimation time of death is one of key task of forensic entomology. Especially interesting is Coleofauna present at all stages of cadaver decomposition. The morphological identification of Coleoptera species from varying life stages to species level is time-consuming and needs highly qualified entomologists. Among different molecular methods of species identification very promising is high-resolution melting PCR. It allows fast single-tube assignment of analyzed sample to species based on amplicon melting profile. The object of this study were different specimens of Coleoptera collected at pig cadavers in Łomna (central Poland) during 2012 - 2014. Specimes were identified to species by experts of corresponding Coleoptera families. From 120 collected specimens belonging to four families and twelve species HRM-PCR correctly identified specimens belonging to three families and eight species.